The Value of Parental Karyotyping in Recurrent Pregnancy Loss Lies in Individual Risk Assessments - Gabriela Popescu-Hobeanu; Simona Serban Sosoi; Mihai Cucu; Ioana Streață; Amelia Dobrescu; Răzvan Pleșea; Anca Lelia Costache; Andreea Iordache; Bianca Petre-Mandache; Ștefania Tudorache; Alexandru Comănescu; Dominic Iliescu; et al. (Medicina)
Background and Objectives: Recurrent pregnancy loss (RPL) is a multifactorial condition, encompassing genetic, anatomical, immunological, endocrine, as well as infectious and environmental factors; however, the etiology remains elusive in a substantial number of cases. Genetic factors linked to RPL include parental karyotype abnormalities (e.g., translocations, inversions, copy number variants), an increase in sperm aneuploidy, fetal microchimerism, severe skewing of X chromosome inactivation, and various gene polymorphisms. Our study aims to explore the value of routine conventional parental karyotyping in couples with RPL. Materials and Methods: A total of 213 couples (426 individuals) with a history of RPL were enrolled in this retrospective study. The peripheral blood samples included in this study were referred to the Human Genomics Laboratory of the University of Medicine and Pharmacy in Craiova, Romania, for conventional cytogenetic analysis between January 2013 and December 2023, by the Outpatient Medical Genetics Clinic of the Emergency Clinical County Hospital of Craiova. Chromosome analysis was performed using standard protocols and karyotypes were reported according to ISCN. Results: Out of 426 patients provided with conventional G-banded chromosome analysis, 410 had a normal karyotype (96.2%) and 16 had chromosome abnormalities (3.8%). The most common chromosomal abnormalities were reciprocal and Robertsonian translocations, with chromosomes 8, 11, 14, and 21 being most frequently involved. A single numerical anomaly was detected (47,XYY). One or multiple chromosomal polymorphisms were identified in 104 subjects (24.4%). In addition, we conducted a stratified analysis of the unselected group and detected chromosome abnormalities in only four cases (0.94%). Conclusions: Our results are consistent with recommendations for paternal karyotyping after an individual risk assessment in instances such as a previous live birth with congenital anomalies and/or the detection of unbalanced chromosomes or a translocation in product of conception or chorionic villi/amniotic fluid samples. In the absence of a positive history, blindly karyotyping couples may prove too expensive and labor intensive, while providing no information on fertility status or live birth rates.